A Hybrid Solid‐State NMR and Electron Microscopy Structure‐Determination Protocol for Engineering Advanced para‐Crystalline Optical Materials. Issue 14 (16th February 2017) - Thomas, Brijith; Rombouts, Jeroen; Oostergetel, Gert T.; Gupta, Karthick B. S. S.; Buda, Francesco; Lammertsma, Koop; Orru, Romano; de Groot, Huub J. M.
Abstract: Hybrid magic‐angle spinning (MAS) NMR spectroscopy and TEM were demonstrated for de novo structure determination of para ‐crystalline materials with a bioinspired fused naphthalene diimide (NDI)–salphen–phenazine prototype light‐harvesting compound. Starting from chiral building blocks with C 2 molecular symmetry, the asymmetric unit was determined by MAS NMR spectroscopy, index low‐resolution TEM diffraction data, and resolve reflection conditions, and for the first time the ability to determine the space group from reciprocal space data using this hybrid approach was shown. Transfer of molecular C 2 symmetry into P 2/ c packing symmetry provided a connection across length scales to overcome both lack of long‐range order and missing diffraction‐phase information. Refinement with heteronuclear distance constraints confirmed the racemic P 2/ c packing that was scaffolded by molecular recognition of salphen zinc in a pseudo‐octahedral environment with bromide and with alkyl chains folding along the phenazine. The NDI light‐harvesting stacks ran orthogonal to the intermolecular electric dipole moment present in the solid. Finally, the orientation of flexible lamellae on an electrode surface was determined. Abstract : Combined forces : Packing of a fused chromophore light‐harvesting material is resolved with a four‐step hybrid approach involving magic‐angle spinning NMR spectroscopy and cryo‐electron microscopy (EM). Chemical shift and distance constraints from NMR data are combined with reflection conditions from the Fourier transform of EM images to overcome heterogeneity and problems with indexing the diffraction and determining the space group.